Self-regulation skills and Academic Integration and their relationship to the Motivation to Learn among Students of the Faculty of Science in Palestinian Universities - Mervat Alnajar (Umm Al-Qura University, 2022)
The study aimed to identify the level of self-regulation skills and the level of academic integration, as well as to identify the level of motivation to learn among students of the Faculty of Science in Palestinian universities, and to identify the nature of the relationship between self-regulation skills and academic integration and motivation to learn among the study sample. The study sample consisted of (250) male and female students from College of Science in Palestinian universities, and the researcher used the scale of self-regulation skills, academic integration and learning motivation scale, all of which were prepared by the researcher. A statistic between academic engagement and motivation to learn.